Arthroscopic Morphology of Labrum Tear in Recurrent Anterior Dislocation of Shoulder - Dung Tran Trung; Manh Nguyen Huu; Tuyen Nguyen Trung; Hieu Pham Trung; Nam Vu Tu; Phuong Nguyen Huy; Lam Tran Quoc; Thai Nguyen Hoang; Sang Nguyen Tran Quang (Journal of Surgery and Surgical Research - Peertechz Publications, 2017)
Objective: Evaluate the characters of labrum tear morphology in recurrent anterior dislocation of shoulder via arthroscopy. Material and method: Retrospective demographic study 55 recurrent shoulder dislocation patients underwent arthroscopic labrum repair in Saint Paul University Hospital and Hanoi Medical University Hospital from 2009 to 2013. Results: 65.5% patients with grade 2 tear with 2-3 cm length; The location of tear is anterior and anterior inferior occupied 81.9%; mobile torn labrum is 50.9% and bone healed labrum is 34.6%. Conclusion: The morphology of labrum tear in recurrent shoulder dislocation is various.